Evidence of Successful Mangrove Conservation Avicennia marina Viewing from Bivalves Diversity in Central Lombok - Ulfah Nurkhaeroni; Agil Al Idrus (Jurnal Biologi Tropis, 2023)
Administratively, the coastal area of Central Lombok Regency is included in the mangrove conservation program which is currently in the process of rehabilitation. Shellfish as one of the associated biota that live in the mangrove ecosystem. This study aims to analyze the diversity (H'), uniformity (E), dominance (D), and abundance (R) of associated biota in the mangrove ecosystem conservation area on the south coast of Central Lombok Regency. Data analysis consisted of determining sampling stations, processing mangrove vegetation data, processing bivalve data, and environmental parameters. The results showed that there were nine types of mangroves, 15 types of bivalves were found. The highest density of mangroves in Dondon was Avicennia marina (84.16%) and the highest relative frequency of mangrove species (66.67%). The lowest mangrove density in Gili Perigi was Rhizophora stylosa (3.1%) and the lowest relative species frequency (6.67%). Furthermore, the highest relative frequency in Tanjung Batutiang is Avicennia marina (30.00%) and the lowest is Avicennia lanata (3.33). While the highest relative frequency in Gili Perigi was Avicennia marina (50.00%) and the lowest was Rhizopora stylosa (6.67%). The highest value of the dominance index on the Dondon Coast was 0.84 and was classified as low, meaning that no species dominated. In conclusion, the Indonesian government has initiated many mangrove Rehabilitation programs through replanting, especially on Lombok Island. This study shows that members of the genus Avicennia marina have the potential to increase the growth and stability of mangrove ecosystems on the south coast of Central Lombok.